Corporate Strategy Analysis in Private Islamic Higher Education Institutions: Implications for Educational Management - Fara Fariha Rodliyana; Agus Zaenul Fitri; Sulistyorini (Journal of Educational Management Research, 2025)
This study aims to examine the implementation of corporate strategy in the development of Sekolah Tinggi Agama Islam (STAI) KH. Muhammad Ali Shodiq Tulungagung, focusing on strategic planning, execution stages, and the types of grand strategies adopted. Employing a qualitative descriptive approach, data were collected through semi-structured interviews, document analysis, and limited observation. Data analysis followed an interactive model, including data condensation, display, and conclusion drawing. The findings reveal that STAI KH. Muhammad Ali Shodiq Tulungagung applies corporate strategies in a contextual and integrated manner, combining selective growth and stability strategies. Key areas of focus include enhancing academic quality, improving institutional governance, and strengthening social relevance. These strategies not only support institutional competitiveness and long-term sustainability but also reflect effective educational management practices, including strategic decision-making, resource optimization, and leadership in higher education. The study highlights that integrating corporate strategy with educational management dimensions is crucial for Islamic higher education institutions to respond effectively to globalization, digitalization, and evolving quality standards.